(untitled) (Movimenta (ISSN 1984-4298), 2016)
This special edition of Movimenta comes about in perfect timing! A unique issue, that perhaps brings some of the most distinguished pieces of research being developed in the United Kingdom and Brazil on different topics related to the field of study of Dance Medicine & Science, was made possible by an invitation from the chief editor of Movimenta, PhD Cibelle Formiga. Cibelle, an astute colleague, seems to have foreseen the importance of such an edition at this moment in time. Thank you very much indeed, Cibelle, for helping us achieve more! We must explain on this preamble why this is such an important edition. It stands out from the ordinary not just because the works the readers will have access to are of high quality, having being written by the very best PhDs, PhDs to be or Masters on this field of study. Mostly of all, it is distinct because behind these expanded summaries there lies the grand opportunity of making the Dance Medicine & Science field of study more visible for an Anglo-Portuguese and Anglo-Brazilian audience.